2022
DOI: 10.21203/rs.3.rs-1243777/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Animal Models for Premature Ovarian Insufficiency Induced by Different Doses of Cyclophosphamide: a Network Meta‑analysis

Abstract: IntroductionCyclophosphamide (CTX), is reported to be extensively used to establish POI animal model. But the most effective dose has not been systematically concluded yet. This systematic review and network meta-analysis is aimed to compare and rank the different doses of cyclophosphamide in the CTX-induced POI rat model.MethodsRandomized controlled trials of CTX-induced rat POI model were searched in four databases from inception to December, 2021. A network meta-analysis was conducted to analyze the data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Z., 2013 ; Nie, X et al, 2018 ). Clinical studies showed that patients in the POF group were found to have significantly higher FSH and LH serum concentrations and lower E 2 serum levels when compared to healthy controls ( Podfigurna, A et al, 2018 ; Qi et al, 2022 ). Our hormone level results are consistent with our previous findings ( Kuang et al, 2014 ; Li et al, 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…Z., 2013 ; Nie, X et al, 2018 ). Clinical studies showed that patients in the POF group were found to have significantly higher FSH and LH serum concentrations and lower E 2 serum levels when compared to healthy controls ( Podfigurna, A et al, 2018 ; Qi et al, 2022 ). Our hormone level results are consistent with our previous findings ( Kuang et al, 2014 ; Li et al, 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study has reported that for the construction of POI mouse models, cyclophosphamide (CTX) (120 mg/kg)/busulfan (12 mg/kg) treatment for at least 2 weeks or cisplatin (2 mg/kg) treatment for more than 10 days was found to be the most effective way to construct POI mice ( 94 ). For the induction of POI rats, a loading dose of 200 mg/kg CTX and a maintenance dose of 8 mg/kg CTX for 14 days is the most effective method ( 95 ). A study has shown that exosomes derived from bone marrow mesenchymal cells (BMSCs) can carry miR-144-5p that can mediate the activation of pI3K/AKT pathway and target ovarian granulosa cells (GCs) damaged by CTX, so as to inhibit GC apoptosis in rats with POI caused by CTX and improve ovarian function ( 96 ).…”
Section: Exosomes and Non-ovarian Cancer Diseasementioning
confidence: 99%